2020
DOI: 10.1016/j.dci.2020.103691
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fenofibrate attenuated high-fat-diet-induced lipid accumulation and inflammation response partly through regulation of pparα and sirt1 in juvenile black seabream (Acanthopagrus schlegelii)

Abstract: An 8-week feeding trail was conducted in Acanthopagrus schlegelii with an initial body weight of 8.34±0.01g. Three isonitrogenous diets were formulated, (1) Control: Title Dietary fenofibrate attenuated high-fat-diet-induced lipid accumulation and inflammation response partly through regulation of pparα and sirt1 in juvenile black seabream (Acanthopagrus schlegelii)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 55 publications
5
20
0
Order By: Relevance
“…In this study, the expression of Il1β , tgfβ and tnfα were significantly increased in Japanese seabass fed high‐fat diet, which indicated high dietary lipid activated inflammation response of fish. Inflammation related gene expressions were also up‐regulated in black seabream, blunt snout bream and tilapia fed high‐fat diet (Dai et al, 2019; Jia et al, 2020; Jin et al, 2020). Previous research reported that high‐fat‐diet‐induced inflammatory response closely associated with endoplasmic reticulum stress (ERS) (Jin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the expression of Il1β , tgfβ and tnfα were significantly increased in Japanese seabass fed high‐fat diet, which indicated high dietary lipid activated inflammation response of fish. Inflammation related gene expressions were also up‐regulated in black seabream, blunt snout bream and tilapia fed high‐fat diet (Dai et al, 2019; Jia et al, 2020; Jin et al, 2020). Previous research reported that high‐fat‐diet‐induced inflammatory response closely associated with endoplasmic reticulum stress (ERS) (Jin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…High‐fat diet firstly induced the production of reactive oxygen species, lipid peroxides and pro‐inflammatory factors (Yin et al, 2020). Long‐term intake of high‐fat diet then activated multiple immune signalling pathways such as c‐jun N‐terminal kinase (JNK), nuclear factor κB (NF‐κB) and toll‐like receptors (TLRs) (Jia et al, 2020, Jin et al, 2020, Wei et al, 2017), and finally induced the DNA damage and apoptosis (Dai et al, 2019). Until now, the tolerance of Japanese seabass to high‐fat diet has not been evaluated, and the molecular mechanisms of high‐fat‐diet‐induced inflammation in Japanese seabass have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In both fish and mammals, pparα is considered to be a master regulator of lipid catabolism and could be activated by fenofibrate (Fabbrini et al, 2010; Jin et al, 2020). Similarly, our results showed that pparα expression was significantly increased in HFD group after fenofibrate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the approaches to increase lipid utilization, for example stimulating lipid catabolism capability, have been a hot research area in fish nutritionists (Jin et al, 2020;Li et al, 2019;Zhao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In Nile tilapia (Oreochromis niloticus) and yellow catfish, fenofibrate could activate Pparα, promote fatty acids beta-oxidation and decrease lipogenesis in liver to significantly reduce fat deposition (Ning et al, 2016;Zheng, Luo, Hu, Pan, & Zhuo, 2015). In black seabream (Acanthopagrus schlegelii), pparα could also be activated by fenofibrate and led to amelioration of inflammation and lipid deposition in liver (Jin et al, 2020). However, in the obscure puffer (Takifugu obscurus), the dietary fenofibrate elevated mRNA expressions in the both lipolysis-and lipogenesis-related genes, and the lipid deposition was also reduced (Su et al, 2021).…”
Section: Introductionmentioning
confidence: 99%